2020
DOI: 10.1039/d0ee01095b
|View full text |Cite
|
Sign up to set email alerts
|

Highly durable fuel cell catalysts using crosslinkable block copolymer-based carbon supports with ultralow Pt loadings

Abstract: Minimizing the use of Pt catalysts in proton exchange membrane fuel cells (PEMFC) is important, considering its high price and scarcity. Herein, we demonstrate novel catalysts for PEMFCs with exceptionally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 50 publications
1
70
0
Order By: Relevance
“…Thus, the apparent HER activity of Pt/rGO and Pt 2 Ir 1 /rGO could effectively reveal their catalytic contributions from the loaded metals themselves. Experimentally, the Pt 2 Ir 1 /rGO catalysts showed far higher overpotental of 193 mV to reach 20 mA•cm To investigate the catalytic contributions from pathway (b), we have incorporated thiocyanate ions (SCN − ) with catalysts, which are known to block and deactivate the Pt and Ir sites under acidic conditions 60,63 . As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the apparent HER activity of Pt/rGO and Pt 2 Ir 1 /rGO could effectively reveal their catalytic contributions from the loaded metals themselves. Experimentally, the Pt 2 Ir 1 /rGO catalysts showed far higher overpotental of 193 mV to reach 20 mA•cm To investigate the catalytic contributions from pathway (b), we have incorporated thiocyanate ions (SCN − ) with catalysts, which are known to block and deactivate the Pt and Ir sites under acidic conditions 60,63 . As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the catalytic contributions from pathway (b), we have incorporated thiocyanate ions (SCN − ) with catalysts, which are known to block and deactivate the Pt and Ir sites under acidic conditions 60 , 63 . As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, photo‐crosslinkable polystyrene‐random‐polyvinylbenzylazide (P(S‐ r ‐N 3 )) ( M n = 2 kDa) polymers were dissolved together in a chloroform solution of each PS‐ b ‐PDMS BCP. [ 10 ] The BCP particles were generated with evaporative emulsion‐based methods. [ 12 ] The chloroform solutions were emulsified with an aqueous solution containing sodium dodecyl sulfate (SDS) surfactants through a Shirashu Porous Glass (SPG) membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The PtFe NPs were encapsulated with a very thin carbon shell (≈1 nm) (Figures S8b,d and S9, Supporting Information), which prevents the dissolution of the NPs and thereby significantly increases the durability of the catalysts. [ 10 ] The loading amounts of Fe and Pt were 5 wt% and 1 wt%, respectively, as measured by inductively coupled plasma optical emission spectroscopy (ICP‐OES). Energy‐dispersive X‐ray spectroscopy (EDS) mapping of the CMC‐PtFe catalysts confirmed that the NPs consisted of Pt and Fe (Figure S8c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation